Draft Annual Plan 1982-83 Volume III Government of Jammu and Kashmir - (:unkn) unknown (Planning Commission, 1981)
Out of the sixth five year plan (1980-35) provision of Rs. 50.94 crores for Major and Medium irrigation projects Rs. 8.44 crores have been spent during 1930-31 the first year. During 1931-82 Rs, 10.90 1 crores have been allotted but-the expenditure is likely to be of the order of Rs. 12.09 crores. After deducting the expenditure for the first two years i.e. 1930-81 and 312981- still Rs. 57.95 crores remain to be spent for the rest of the three years of 6th Five year Plan (1930-35) 1932-35, 1933-84 and 1984-85. For annual plan 1932—35 an amount of Rs. 1591 crores have boon proposed. Out of Rs. 1 5.91 crores Rs. 5.86 crores have been proposed to be seasick spent on Ravi 4 Ravi Irrigation Complex, a major irrigation scheme, Rs. 4.05 crores on medium irrigation schemes of Jammu province and Rs. 4.00 crores for medium irrigation schemes of Kashmir Province.
Government of Jammu and Kashmir
Planning and Development Department Jammu
Keywords: Government of Jammu and Kashmir; Minor Irrigation; Flood control; Command Area; Planning and Development Department Jammu; Major & Medium Irrigation; Ravi Tawi Irrigation; Power; Large & Medium Industries; Village Industries; Mining; Road Transport Corporations; State Motor Garages; Tourism; Parks & Gardens; Roads and Bridges.